2020
DOI: 10.1371/journal.pgen.1009000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recessive Mutation in SPEG Causes Early Onset Dilated Cardiomyopathy

Abstract: Dilated cardiomyopathy (DCM) is a common cause of heart failure and sudden cardiac death. It has been estimated that up to half of DCM cases are hereditary. Mutations in more than 50 genes, primarily autosomal dominant, have been reported. Although rare, recessive mutations are thought to contribute considerably to DCM, especially in young children. Here we identified a novel recessive mutation in the striated muscle enriched protein kinase (SPEG, p. E1680K) gene in a family with nonsyndromic, early onset DCM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Cysteine sulfinic acid decarboxylase (CASD) is an important biosynthetic enzyme for taurine. The low activity of CASD is more likely to cause taurine deficiency which eventually leads to heart failure accompanied by myocardial fibrosis [41, 42]. Histamine, the product from histidine metabolism, is synthesized via catalytic decarboxylation of histidine by histidine decarboxylase (HDC) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine sulfinic acid decarboxylase (CASD) is an important biosynthetic enzyme for taurine. The low activity of CASD is more likely to cause taurine deficiency which eventually leads to heart failure accompanied by myocardial fibrosis [41, 42]. Histamine, the product from histidine metabolism, is synthesized via catalytic decarboxylation of histidine by histidine decarboxylase (HDC) [43].…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR has also been applied to interrogate cardiac diseases, such as dilated cardiomyopathy (Briganti et al, 2020;Levitas et al, 2020;Rebs et al, 2020). Creation of gene reporters has helped characterize cardiac lineage subpopulations through dual tagging of TBX2 and NKX2-5 (Zhang et al, 2019), while tagging of a series of sarcomere-related genes aided their visualization at the sarcomere in real time (Roberts et al, 2019).…”
Section: Crispr Editing Of Pluripotent Stem Cellsmentioning
confidence: 99%
“…Underlying these clinical phenotypes, cellular and molecular hallmarks of CNM include increased central nucleation of myofibers and variation in myofibers size, and disruptions in triadic structure and E-C coupling [ 10 , 44 , 45 ]. To date, 20 patients have been identified with SPEG mutations [ 23 , 44 , 46 , 47 , 48 , 49 ]. Figure 1 shows the location and mutation type of all reported SPEG variants.…”
Section: Speg Mutations In Myopathies and Cardiomyopathiesmentioning
confidence: 99%
“…Five additional patients from a single family showing isolated DCM without myopathy was recently described by Levitas et al [ 47 ] carrying homozygous missense mutation (c.5038G>A, p.Glu1680Lys) in the serine/threonine protein kinase (SK)-1 domain of SPEG. Functional studies in induced pluripotent stem cell-derived cardiomyocytes showed aberrant calcium homeostasis, impaired contractility, and sarcomeric disorganization [ 47 ]. We recently identified three patients with a homozygous in-frame deletion (c.9028_9030delGAG, p.Glu3010del) in the SK-2 domain of SPEG [ 49 ].…”
Section: Speg Mutations In Myopathies and Cardiomyopathiesmentioning
confidence: 99%